Curative effect of Plumbago indica root extract on thioacetamide induced hepatotoxicity in experimental rats - Eldhose Binil; Kuriakose Jayesh; Latha Mukalel Sankunni (International Journal of Phytomedicine, 2017)
The root parts of Plumbago indica is widely used in the Indian Ayurvedic traditional system. The study was designed to evaluate the hepato curative activity Plumbago Indica (PLBM) methanolic root extracts at different doses (100 and 200 mg/kg bw) against thioacetamide induced liver damage in albino wistar rats. Liver damage was induced by administration of Thioacetamide (100 mg/kg bw) and was assessed by evaluating the activity of liver-function marker enzymes, antioxidant enzymes and lipid peroxidation. The liver sections were evaluated for histopathological changes. PLBM significantly (p ≤ 0.05) reversed the elevation of serum liver enzymes and hepatic levels of antioxidant markers. Histopathological findings also confirmed the curative effect of Plumbago Indica in a dose dependent manner. Thus this study scientifically rationale the use of Plumbago indica root as a promising drug against various liver disorders.